Cellular microenvironment influences the ability of mammary epithelia to undergo cell cycle. - Alexa I Jeanes; Apolinar Maya-Mendoza; Charles H Streuli (PLoS ONE)
The use of cell culture models is a principal and fundamental technology used in understanding how mammalian cells work. However, for some cell types such as mammary epithelia, the lines selected for extended culture are often transformed or have chromosomal abnormalities, while primary cultures have such a curtailed lifespan that their use is restricted. For example, mammary luminal epithelial cells (MECs) are used to study mechanisms of breast cancer, but the proliferation of primary cell cultures is highly limited. Here we describe the establishment of a new culture system to allow extended analysis of cultures of primary mouse MECs. In 2D monolayer culture, primary MECs showed a burst of proliferation 2-3 days post isolation, after which cell cycle decreased substantially. Addition of mammary epithelial growth factors, such as Epidermal Growth Factor, Fibroblast Growth Factor-2, Hepatocyte Growth Factor, and Receptor Activator for Nuclear Factor κB Ligand, or extracellular matrix proteins did not maintain their proliferation potential, neither did replating the cells to increase the mitogenic response. However, culturing MECs directly after tissue extraction in a 3D microenvironment consisting of basement membrane proteins, extended the time in culture in which the cells could proliferate. Our data reveal that the cellular microenvironment has profound effects on the proliferative properties of the mammary epithelia and is dominant over growth factors. Moreover, manipulating the cellular environment using this novel method can maintain the proliferative potential of primary MECs, thus enabling cell cycle to be studied as an endpoint after gene transfer or gene deletion experiments.